THE INFLUENCE OF WORK STRESS ON EMPLOYEE PERFORMANCE AT PT. BANK MANDIRI (PERSERO) TBK. REGION I NORTH SUMATERA RETAIL FUNDING UNIT - Rachmawati, Yeni; Silalahi, Flora; Amika, Mimi (SEAN Institute, 2023)
Work stress is a feeling of anxiety, tension, or pressure that employees experience while working. Work stress can be caused by various factors, such as a heavy workload, an unfavorable work environment, or conflicts with coworkers. Excessive work stress can interfere with a person's ability to adapt to the work environment, so it can cause a decrease in employee performance. Employee performance is the result of work achieved by employees in a certain period. Employee performance can be measured by various indicators, such as work productivity, work quality, and job satisfaction. This study aims to determine whether work stress affects the performance of employees of PT Bank Mandiri (Persero) Tbk. Region I Sumatra Retail Funding Unit. This research uses quantitative methods by distributing questionnaires to 36 employees of PT. Bank Mandiri (Persero) Tbk. Region I Sumatra Retail Funding Unit. The results showed that work stress affects the performance of employees of PT Bank Mandiri (Persero) Tbk. Region I Sumatra Retail Funding Unit. The effect of job stress on employee performance is 59.1%, while 40.9% is influenced by other variables not examined. The conclusion of this study shows that job stress can be a factor that reduces employee performance. Therefore, it is important for companies to manage employee work stress in order to improve employee performance.